Regulatory T Cells in Mycobacterium tuberculosis Infection - Cardona, Paula; Cardona, Pere-Joan (Frontiers in Immunology, 2019)
Anti-inflammatory regulatory T cells have lately attracted attention as part of the immune response to Mycobacterium tuberculosis infection, where they counterbalance the protective but pro-inflammatory immune response mediated by Th17 cells and especially by the better-known Th1 cells. In chronic infectious diseases there is a delicate balance between pro- and anti-inflammatory responses. While Th1 and Th17 are needed in order to control infection by Mycobacterium tuberculosis, the inflammatory onset can ultimately become detrimental for the host. In this review, we assess current information on the controversy over whether counterbalancing regulatory T cells are promoting pathogen growth or protecting the host.